Destruction of per/poly-fluorinated alkyl substances by magnetite nanoparticle-catalyzed UV-Fenton reaction. Issue 11 (23rd September 2022) - Schlesinger, Danielle R.; McDermott, Collin; Le, Nam Q.; Ko, Jesse S.; Johnson, James K.; Demirev, Plamen A.; Xia, Zhiyong
Abstract : Novel economically-sustainable and environmentally-friendly technologies for per- and poly-fluoroalkyl substance (PFAS) destruction are becoming increasingly important as PFAS contamination has increased in drinking water throughout the globe. Abstract : Novel economically-sustainable and environmentally-friendly technologies for per- and poly-fluoroalkyl substance (PFAS) destruction are becoming increasingly important as PFAS contamination has increased in drinking water throughout the globe. UV-Fenton chemistry catalyzed by nanosize magnetite (Fe3 O4 ) particles in aqueous environments is a promising method for production of reactive oxygen species (ROS), capable of disrupting PFAS carbon-fluorine bonds. Here we demonstrate greater than 90% degradation efficiency for a wide variety of PFAS compounds by ROS generated in a UV-Fenton reaction, involving naturally-occurring Fe3 O4 nanoparticles. In order to demonstrate that ROS are indeed formed under our experimental conditions, we utilized a fluorescent probe to confirm the presence of ROS in the reaction solution. PFAS destruction efficiency is increased at elevated pH levels; however, by varying both the Fe3 O4 and hydrogen peroxide (H2 O2 ) concentrations in solution, high efficiency can be achieved at neutral pH conditions, like those found in drinking water. PFAS destruction occurred with UV exposure times on the order of minutes. Nano Fe3 O4 retained its oxidation state and catalytic efficiency after multiple cycles of PFAS destruction, indicating that the material is reusable. High resolution mass spectrometry was utilized to demonstrate destruction efficiency and to identify the degradation products. ROS generation utilizing naturally-occurring Fe3 O4 nanoparticles has been shown to be an efficient method for PFAS destruction with potential scalability for drinking water decontamination.